How to confuse with statistics or: the use and misuse of conditional probabilities - Gerd Gigerenzer; Walter Krämer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
The article shows by various examples how consumers of statistical information may be confused when this information is presented in terms of conditional probabilities. It also shows how this confusion helps others to lie with statistics, and it suggests how either confusion or lies can be avoided by using alternative modes of conveying statistical information.
Keywords: 519; Statistische Methode; Manipulation; Theorie; Bedingte Wahrscheinlichkeiten